Effects of Orexin 2 Receptor Activation on Apnea in the C57BL/6J Mouse - Moore, Michael W. (Respir Physiol Neurobiol, 2014)
BACKGROUND: The hypothesis was that an orexin 2 receptor (OX2R) agonist would prevent sleep-related disordered breathing. METHODS: In C57BL/6J (B6) mice, body plethysmography was performed with and without EEG monitoring of state (wakefulness, NREM and REM sleep). Outcome was apnea rate/hr during sleep-wake states at baseline and with an intracerebroventricular administration of vehicle, 4nMol of agonist OB(DL), and 4nMol of an antagonist, TCS OX2 29. RESULTS: A significant reduction (p=0.035; f=2.99) in apneas/hour occurred, especially with the agonist. Expressed as a function of the change from baseline, there was a significant difference among groups in Wake (p=0.03, f=3.8), NREM (p=0.003, f= 6.98) and REM (p=0.03, f= 3.92) with the agonist reducing the rate of apneas during sleep from 29.7± 4.7 (M+/− SEM) to 7.3±2.4 during sleep (p=0.001). There was also a reduction in apneas during wakefulness. Administration of the antagonist did not increase event rate over baseline levels. CONCLUSIONS: The B6 mouse is a preclinical model of wake-and sleep-disordered breathing, and the orexin receptor agonist at a dose of 4nMol given intracerebroventricularly will reduce events in sleep and also wakefulness.